Common use of high doses of antipsychotic medications in older Asian patients with schizophrenia (2001–2009). (13th August 2013) - Xiang, Yu‐Tao; Li, Yan; Correll, Christoph U.; Ungvari, Gabor S.; Chiu, Helen F.K.; Lai, Kelly Y. C.; Tang, Quan‐Sheng; Hao, Wei; Si, Tian‐Mei; Wang, Chuan‐Yue; Lee, Edwin H. M; He, Yan‐Ling; et al.
<x xml:space="preserve">Abstract</x> Objective This study aimed to examine the use of high doses of antipsychotic medications (≥600 mg/day chlorpromazine equivalent) in older Asian patients with schizophrenia and its demographic and clinical correlates. Method Information on hospitalized patients with schizophrenia aged ≥50 years was extracted from the database of the Research on Asian Psychotropic Prescription Patterns study (2001–2009). Data on 2203 patients in six Asian countries and territories, including China, Hong Kong, Japan, Korea, Singapore and Taiwan, were analyzed. Socio‐demographic and clinical characteristics and antipsychotic prescriptions were recorded. Results The frequency for high‐dose antipsychotic medications was 36.0% overall, with 38.4% in 2001, 33.3% in 2004 and 36.0% in 2009. Multiple logistic regression analysis of the whole sample showed that compared to patients receiving low‐medium antipsychotic doses, those on high doses had a longer illness duration (odds ratio (OR): 2.0, 95% confidence interval (CI):1.2–3.3, p = 0.008), were more likely in the 50–59‐year group (OR: 0.95, 95% CI: 0.94–0.97, p < 0.001), more often had current positive (OR: 1.5, 95% CI: 1.2–1.8, p < 0.001) or negative symptoms (OR: 1.3, 95% CI: 1.03–1.6, p = 0.03), and more commonly received antipsychotic polypharmacy (OR: 5.3, 95% CI: 4.1–6.7, p < 0.001). Extrapyramidal symptoms (p = 0.25) and tardive dyskinesia (p = 0.92) were not more frequent in the high‐dose group. Conclusions High doses of antipsychotic medications were used in more than one third of older Asian patients with schizophrenia. The reasons for the frequent use of high antipsychotic doses in older Asian patients warrant further investigation. Copyright © 2013 John Wiley & Sons, Ltd.